LOS ESTADOS INMADUROS DE 7 ESPECIES NEOTROPICALES DEL GENERO DASYBASIS MACQUART (TABANIDAE, DIPTERA, INSECTA) (Acta Entomológica Chilena, 2022)
Larvae and pupae of Dasybasis andícola (Philippi), D. canipilis Kroeber, D. opaca (Bréthes), D. testaceomaculata(Macquart), and pupa of D. chilensis (Macquart) are described; larva and pupa of D. fairchildiCoscaron 8c Philip and D. nigra (Enderlein) are redescribed. A genus diagnosis based on immatures,keys and illustrations are included.